Aspect, communicative appeal, and temporal meaning in Biblical Hebrew verbal forms - Bergström, Ulf, 1974- (University Park, Pennsylvania : Eisenbrauns, 2022)
"Offers a new explanation for the expression of tense and aspect in Biblical Hebrew, demonstrating that the verbal forms have basic aspectual and derived temporal meanings"--
Introduction -- Comments on the state of research -- A theory of aspect and tense -- Progressive and resultative verbs in Biblical Hebrew -- Communicative appeal and the semantics of the Biblical Hebrew verb -- Conclusion.
Includes bibliographical references and index.
JSTOR
Keywords: Hebrew language -- Verb; Hebrew language -- Aspect; Hebrew language -- Tense; Hebrew language -- Semantics; Hebrew language -- Aspect; Hebrew language -- Semantics; Hebrew language -- Tense; Hebrew language -- Verb